EFFECT OF INVESTORS' OVERCONFIDENCE AND MENTAL ACCOUNTING ON INVESTMENT PERFORMANCE OF DEPOSIT MONEY BANKS IN NIGERIA - Isiaka Olalekan Lasisi; Adetokun Akeem Abiodun; Luka Mailafia, PhD; Isah Shittu, PhD; Musa Tijani. Bashir, PhD (Gusau Journal of Accounting and Finance)
Behavioral finance theory documents that the actions of individual investors have demonstrated that individuals appear to respond to and perceive the same information differently, generating cognitive biases. It is against this backdrop that this study empirically examines the effect of mental accounting and investors' overconfidence on the investment performance of deposit money banks in Nigeria. The study used 960 daily observations on the population of thirteen (13) and a sample size of eight (8) deposit money banks in Nigeria that paid annual dividends from the period 2013 to 2022. The study employed a secondary source of data collection and was gathered from the monthly share market data and annual financial reports from 2013 to 2022. The study data were analyzed through descriptive statistics, correlation analysis, and the multiple regression model to test the formulated hypothesis for the study. after conducting the diagnostic tests such as the mean VIF test and Hettest, the study established that the Ordinary Least Squares (OLS) model is the study-appropriate model for the study. The findings of the study showed that mental accounting and the overconfidence of investors have a positive and significant effect on the investment performance of deposit money banks in Nigeria. Based on the results of the study, it is recommended that mental accounting and overconfidence should be considered during financial investment decision-making processes because it has been empirically established that they both, had a favorable and significant effect on investment performance.